Water Quality Assessment for Tigris River Through Salah Al-Din Province, Iraq Using Remote Sensing Techniques - Qassim, Noorhan M.; Ahmed, Bushra A. (Iraqi Journal of Physics, 2020)
water quality assessment is still being done at specific locations of major concern. The use of Geographical Information System (GIS) based water quality information system and spatial analysis with Inverse Distance Weighted interpolation enabled the mapping of water quality indicators along Tigris river in Salah Al-Din government, Iraq. Water quality indicators were monitored by taking 13 river samples from different locations along the river during Winter season year 2020. Maps of 10 water quality indicators. This meant that the specific water quality indicator and diffuse pollution characteristics in the basin were better illustrated with the variations displayed along the course of the river than conventional line graphs. Creation of water quality maps would enhance surveillance, implementation of standards and regulations for better management and control of pollution.